A rare case of jejunal adenocarcinoma with brain metastasis - Harish, M.; Hariprasad, N.; Kannan, R. (International Surgery Journal, 2021)
Small bowel malignancies are rare entity, with adenocarcinoma being one of common type along with neuroendocrine tumours. Associated with Crohns, celiac disease, FAP and HNPCC. Jejunal adenocarcinoma produce vague symptoms, accounting for late presentation leading to difficult and delayed diagnosis in favour of poor prognosis. Diagnosis is established by CECT abdomen and CEA levels. Ro resection with regional lymphadenectomy and jejunojejunal anastomosis is preferred followed by adjuvant FOLFOX chemotherapy. Here we presenting a 68 years old male, anaemic with vague abdominal pain for 3 months, CECT showed malignant wall thickening involving 10 cm of proximal jejunal loop with no enlarged lymph nodes and CEA was elevated. Proceeded with laparotomy, an irregular hard mass of 10×10 cm involving 20 cm of jejunum with transverse colon infiltration with multiple mesenteric nodes found, composite resection with jejunojejunostomy and colocolic anastomosis done. Histopathology showed poorly differentiated jejunal adenocarcinoma with colonic infiltration with reactive nodes and post operatively on day 7, patient developed seizures and weakness of left upper and lower limbs, MRI brain showed solitary metastasis 2×2 cm in right frontal region and PET CT showed brain metastasis and multiple intraabdominal lymph node, lung and prostate metastasis, planned SBRT for brain metastasis and palliative chemotherapy. Lymph node, liver and peritoneum are common site of metastasis for small bowel adenocarcinoma, very rarely brain metastasis can occur in short time and to be considered if neurological symptoms occur pre and postoperatively.